(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
Ethnic, cultural and spiritual views and religious beliefs of people who lived in antroponyms in ancient times have been preserved and reached to us. On the genetic basis of names can be expressed different outlines, concepts related to nouns. In the center of this imagination is also a person, pictures and habits characteristic of the historical period in which he or she lived, dreams and hopes are expressed. A name is one of the phenomena that occupy a special place in a person’s life. In artistic works, too, the choice of a name for the heroes requires a little reflection. The name of some heroes is considered an important tool in revealing the idea expressed in the artistic works. The article covers some anthroponyms used in oral epic and fairy tales, classical literature and examples of modern literature and their meaning, the connection of the hero with the fate of his or her name, the events described the lingvoculturological aspects of anthroponyms in the artistic work.